SURVIVAL STRATEGY OF KERIS CRAFTSMEN IN AENG TONG-TONG VILLAGE, SARONGGI DISTRICT, SUMENEP REGENCY - Ela Riana, Denisa; Sri Rahayuningsih, Eni (Universitas Islam Lamongan, 2024)
This study aims to analyze the survival strategies of keris craftsmen in Aeng Tong-Tong Village, Saronggi District, Sumenep Regency. This study uses a qualitative phenomenological method. The selected informants are the keris craftsman coordinator and the owner of the keris craft industry. The data collection techniques used are interviews and documentation in the keris craft industry in Aeng Tong-Tong Village. In this study, data validity testing was used through source triangulation which was then analyzed and conclusions were drawn. The results of the study indicate that the survival strategy of keris craftsmen in Aeng Tong-Tong Village utilizes assets or capital, including human capital, natural capital, financial capital, physical capital and social capital.